2023
DOI: 10.1007/s40264-023-01301-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety Analysis of the ChAdOx1-nCoV-19 Corona Virus Vaccine: Results from a Prospective Observational Study in Priority Vaccinated Groups in North India

Abstract: Introduction Various vaccines for protection against COVID-19 were provided emergency approval in late 2020 to early 2021. There is a scarcity of long-term safety data for many of these. Objective The main aim of this study is to provide the one-year safety results of the ChAdOx1-nCoV-19/AZD1222 vaccine and determine the risk factors of adverse events of special interest (AESIs) and persistent AESIs. Methods This was a prospective observational study conducted from February 2021 to April 2022 in a tertiary hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Interestingly, upon the administration of the booster shot of a different platform, the symptoms improved substantially. 24 Kaur et al, 22 , 25 studied COVID-19 vaccine recipients 1 year post vaccination and observed high rates of long COVID/long-term AEs in those who got vaccinated after COVID-19 infection compared to whom immunized before COVID-19 infection. Nonetheless, we found no significant difference in terms of vaccine or infection priority as 39% (n = 16) of the individual who experienced long-COVID/long-Vax, developed COVID-19 infection before vaccination whereas 36.58% (n = 15) who got COVID-19 after vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, upon the administration of the booster shot of a different platform, the symptoms improved substantially. 24 Kaur et al, 22 , 25 studied COVID-19 vaccine recipients 1 year post vaccination and observed high rates of long COVID/long-term AEs in those who got vaccinated after COVID-19 infection compared to whom immunized before COVID-19 infection. Nonetheless, we found no significant difference in terms of vaccine or infection priority as 39% (n = 16) of the individual who experienced long-COVID/long-Vax, developed COVID-19 infection before vaccination whereas 36.58% (n = 15) who got COVID-19 after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In 24.39% of the subjects, no documented history of COVID-19 infection or symptoms was recorded. Moreover, Kaur et al 22 , 25 found that hypothyroid individuals had an increased risk of long-COVID and long term AEs. In line with their results, the total prevalence of hypothyroidism in our data was 7.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Women, individuals with comorbidities such as hypothyroidism, and those with a history of COVID-19 should be informed about the protective benefits of vaccines as well as the risks of adverse events post-vaccination. Compared to further large-scale promotion, an individualized vaccination strategy may be a better choice for public health safety [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, patients of hypothyroidism were observed to be at increased risk of adverse events following immunisation, long COVID‐19 as well as adverse events of special interest after COVID‐19 vaccine [3, 12]. Vaccine received after recovery from COVID‐19 was shown as an independent risk factor of adverse events and persistent adverse events [12].…”
Section: Discussionmentioning
confidence: 99%